(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Transient overvoltage in power systems is one of the most important issues to be considered for system stability. Switching surges is an important reasons that cause transient overvoltage. This paper presents a full study of the high-voltage line connecting KHOMS and GMMRA substations. The study utilizes the Alternative Transient Program (ATP) to compute the transient overvoltage due to switching surges (line closing and re-closing); as well as presenting the usage of surge arrester to reduce the upper limit of transient overvoltage. The results present the positive effect of using surge arrester switching element to limit transient overvoltage and keep it at certain level; in addition to damping the isolation in the voltage waveform.